PENERAPAN AKAD GADAI DALAM PRAKTEK PEMBELIAN BARANG LELANG KREDIT PERSPEKTIF HUKUM EKONOMI SYARIAH (Studi Kasus di Pegadaian Syariah Jokotole Pamekasan) - Sari, Rina Tri Puspita (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
ABSTRACTThe thesis entitled "Application of Pawn Contracts in Goods Purchasing Practices for Sharia Economic Law Perspective Credit Auction" (Case Study in Jokotole Pamekasan Syariah Pawnshop) is motivated by the sale and purchase of credit system gold auction items with the condition that the items purchased are deposited in Jokotole Pamekasan Sharia Pegadaian as collateral and processed as sharia mortgage in general because the goods purchased by the customer are goods belonging to the Jokotole Pamekasan Sharia Pawnshop that he bought with debt. This study aims to analyze the procedures for the application of the mortgage agreement in the practice of buying credit auction items at Jokotole Pamekasan Syariah Pawnshop and to analyze the application of the mortgage agreement in the practice of purchasing goods auctions for Islamic Economic Law Perspective CreditThe research method used in this study is a qualitative field research method, which is sourced from research informants obtained at the time of conducting research at Jokotole Pamekasan Syariah Pawnshop and supported by data that can be strengthened by literature as a supporter. This research is descriptive qualitative, using data collection techniques through interviews, observation, and documentation. The approach used is juridical sociology which is then analyzed using inductive thinking patterns.Based on the results of research in the field related to the Application of Mortgage Contracts in the Practice of Purchasing Credit Auction Goods beginning with the auction process of gold collaterals that have matured in public then auction sales with conditional credit with the mortgage system, the goods purchased by customers are requested to be deposited at Pegadaian Syariah Jokotole Pamekasan as a guarantee to obtain debt, the procedure is exactly the same as the gold mortgage procedure in general. The application of the Pawn Agreement in the practice of buying auctions of credit is part of the procedure in accordance with Islamic law both described in the Qur'an, hadith, muamalah fiqh, KHES and DSN-MUI fatwa but there are some procedures that are contrary to the applicable rules . Moreover, this system is more socialized in the community because it can make it easier for people to get gold as a long-term investment with a credit system.Â Key Word : Pawn Contracts, Goods Purchasing Practices, and Sharia Economic Law.